Seed Quality of Rice Hybrids and their Parental Lines Produced in Different Agro-Climatic Zones of India - HUYNH VAN NGHIEP,; ASHOK GAUR,; O.K. SHARMA, (Seed Research, 2026)
Forty five seed samples of hybrids and parental lines of rice (Oryza sativa) collected from different agro-climatic zones of India, were evaluated for their quality. Out of these samples thirteen had germination below Minimum Seed Certification Standard (MSCS), in which two A lines of hybrids 505 and 509 had very low germination of 25 and 26 per cent, respectively. Nevertheless, there was no specific pattern or relationship of seed germination to a particular type of parental line or hybrid. Ten seedbone fungi ie. Bipolaris oryzae, Alternaria padwickii, Curvularia lunata, Sarocladium oryzae, Fusarium moniliforme, Fusarium pallidoroseum, Alternaria alternata, Aspergillus spp. Penicillium spp. and Rhizopus spp. were found to be associated with these seed lots. The most predominant among them were Bipolaris oryzae, Alternaria padwickii and Curvularia lunata, the incidence of which was considerably higher in R and B lines as compared to hybrids and A lines.